PENDIDIKAN ISLAM DI INDONESIA SEBELUM PROKLAMASI KEMERDEKAAN - M Rusdi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
Islamic education is a way to spread the Islamic teachings. Therefore, to establish Islamic educational institutions must be a program for Muslims. For the first time, Islamic education in Indonesia was conducted traditionally. It was conducted between the Islamic traders as teachers and the society who wanted to buy something as students. The traders also conducted al-da‘wah bi al-hāl (showing good behavior to the society). Therefore, the society was interested in the Islamic traders who brought also the Islamic teaching. Educational method used at that time was sorogan. Students came to the teacher to study. The teachers read and explained their materials to their students and students heard the materials and tried to memorize them. The method then developed to classical system through ma‘had or pesantren or boarding schools. The boarding school system keep develop up to the present time, especially in Indonesia.